ANALISIS TINGKAT KEBUTUHAN MODAL BAGI USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KECAMATAN LIMBOTO KABUPATEN GORONTALO - Srihantuti Paramata; Regina Pontoh (Universitas Muhammadiyah Gorontalo, 2021)
This research aims to: determine and analyze the level of capital requirements for Micro, Small and Medium Enterprises (MSMEs) in Gorontalo Regency. The research method uses a qualitative research approach with qualitative descriptive research. The results based on research findings show that: 1) Of the 50 respondents studied, only 9 respondents or 18% of MSMEs have applied for credit to banks for business development, 2) The level of capital development needs most of it comes from bank credit, with the amount of around Rp. 5,000,000 – Rp. 10,000,000, 3) The ability of MSME Entrepreneurs for the installment payment period is under 3 years with the installment amounting to Rp. 200,000 – Rp. 300,000/month, and 4) The obstacles in applying for credit to banks for MSMEs are high interest rates and heavy credit collateral requirements.